Handbook of the Sociology of Mental Health
XXI, 636 p. 29 illus.
Keywords: This second edition of the Handbook of the Sociology of Mental Health features theory-driven reviews of recent research with a comprehensive approach to the investigation of the ways in which society shapes the mental health of its members and the lives of those who have been diagnosed as having a mental illness The award-winning Handbook is distinctive in its focus on how the organization and functioning of society influences the occurrence of mental disorder and its consequences. A core issue that runs throughout the text concerns the differential distribution of mental illness across various social strata, defined by status characteristics such as gender, race/ethnicity, socioeconomic status, and age. The contributions to this volume shed light on the social, cultural, and economic factors that explain why some social groups have an elevated risk of disorder. They also address the social repercussions of mental disorder for individuals, including stigmatization within the larger society, and for their families and social networks. The second edition of this seminal volume includes substantial updates to previous chapters, as well as seven new chapters on: -The Individual’s Experience of Mental Illness.--The Medicalization of Mental Illness.---Age, Aging, and Mental Health.- -Religion and Mental Health.- -Neighborhoods and Mental Health.- -Mental Health and the Law—and Public Beliefs about Mental Illness. .